Anticancer applications of phytochemicals in gastric cancer: Effects and molecular mechanism - Liang, Zhaofeng; Xu, Yumeng; Zhang, Yue; Zhang, Xinyi; Song, Jiajia; Qian, Hui; Jin, Jianhua (Frontiers in Pharmacology, 2023)
Gastric cancer (GC) is the fourth most common malignant cancer and is a life-threatening disease worldwide. Phytochemicals have been shown to be a rational, safe, non-toxic, and very promising approach to the prevention and treatment of cancer. It has been found that phytochemicals have protective effects against GC through inhibiting cell proliferation, inducing apoptosis and autophagy, suppressing cell invasion and migration, anti-angiogenesis, inhibit Helicobacter pylori infection, regulating the microenvironment. In recent years, the role of phytochemicals in the occurrence, development, drug resistance and prognosis of GC has attracted more and more attention. In order to better understand the relationship between phytochemicals and gastric cancer, we briefly summarize the roles and functions of phytochemicals in GC tumorigenesis, development and prognosis. This review will probably help guide the public to prevent the occurrence and development of GC through phytochemicals, and develop functional foods or drugs for the prevention and treatment of gastric cancer.